The influence of tyre characteristics on measures of rolling performance during cross-country mountain biking - Macdermid, P. W.; Fink, P. W.; Stannard, S. R. (Journal of Sports Sciences, 2015)
This investigation sets out to assess the effect of five different models of mountain bike tyre on rolling performance over hard-pack mud. Independent characteristics included total weight, volume, tread surface area and tread depth. One male cyclist performed multiple (30) trials of a deceleration field test to assess reliability. Further tests performed on a separate occasion included multiple (15) trials of the deceleration test and six fixed power output hill climb tests for each tyre. The deceleration test proved to be reliable as a means of assessing rolling performance via differences in initial and final speed (coefficient of variation (CV) = 4.52%). Overall differences between tyre performance for both deceleration test (P = 0.014) and hill climb (P = 0.032) were found, enabling significant (P < 0.0001 and P = 0.049) models to be generated, allowing tyre performance prediction based on tyre characteristics. The ideal tyre for rolling and climbing performance on hard-pack surfaces would be to decrease tyre weight by way of reductions in tread surface area and tread depth while keeping volume high.